2010
DOI: 10.1177/1948550610390051
|View full text |Cite
|
Sign up to set email alerts
|

Anger as Seeing Red

Abstract: A class of metaphors links the experience of anger to perceptions of redness. Whether such metaphors have significant implications for understanding perception is not known. In Experiment 1, anger (versus sadness) concepts were primed and it was found that priming anger concepts led individuals to be more likely to perceive the color red. In Experiment 2, anger states were directly manipulated, and it was found that evoking anger led individuals to be more likely to perceive red. Both experiments showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 37 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Red is typically associated with high arousal states [51,52], anger [53] and danger [54]; red has also been associated with Tae Kwando match outcome [55]. Conversely, blue and green are perceived as calming [22], only slightly arousing [52], and in congruence with our findings have been shown to be perceived as more pleasant than red [52].…”
Section: Discussionsupporting
confidence: 80%
“…Red is typically associated with high arousal states [51,52], anger [53] and danger [54]; red has also been associated with Tae Kwando match outcome [55]. Conversely, blue and green are perceived as calming [22], only slightly arousing [52], and in congruence with our findings have been shown to be perceived as more pleasant than red [52].…”
Section: Discussionsupporting
confidence: 80%
“…For example, preferences for white versus black should possess relevance in understanding individual differences in positively valenced thoughts (Meier, Robinson, & Clore, 2004), morality (Sherman & Clore, 2009), and perhaps interpersonal functioning (Frank & Gilovich, 1988). Similarly, we would expect preferences for the color red over blue to predict anger and aggression (Fetterman, Robinson, Gordon, & Elliot, 2011). Indeed, we regard a metaphoric approach to personality as an especially generative one in answering important questions concerning how and why people differ from each other (Robinson & Fetterman, in press), particularly given the extensive corpus of linguistic metaphors collected and analyzed by metaphor scholars (Gibbs, 1994; Lakoff & Johnson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that colour influences the categorical judgement of emotional expression and, specifically, that red hue is associated with a bias towards angry judgements. Fetterman et al [20] showed that priming anger concepts (versus sadness) led participants to be more likely to perceive the colour red. Taken together, these findings suggest a clear association between the colour red and perceptions of anger, possibly related to the role of facial reddening as a natural signal of anger [21].…”
Section: Discussionmentioning
confidence: 99%